PEMBELAJARAN PRA PRODUKSI MUSIK MELALUI KEGIATAN STUDENTDAY MUSIK MODERN DI SMA PLUS PGRI CIBINONG - Kusumah, Satria Manggala; Mas Aditya Andriyanto, Raden; Martiati, Lucy (Jurnal Penelitian Musik, 2023)
Abstract: The aim of the study is to gather more in-depth data about how Learning Music Production through "Modern Music StudentDay" Activities in SMA Plus PGRI Cibinong. The method used in this study is a qualitative research method by using descriptive qualitative. The result of the study from learning music production through "Modern Music StudentDay" activities in SMA Plus PGRI Cibinong viewed from the pre-production stage is the process of creating songs,. There is a learning component to support the learning process of music production in terms of pre-production, namely the existence of objectives, materials, methods, media and evaluation of learning. The learning material is; (1) Make determine the theme of the song; (2) Create song lyrics; (3) Create a melodic riff for a song. These material is to prepare for the music recording stage later on. The learning method used is lecture method, demonstration method and discussion method. Learning evaluation, educators do not carry out learning evaluations in the form of assessing the results of student learning outcomes data which is carried out systematically and continuously.